Characteristics and source identification of heavy metals in abandoned coal-mining soil: a case study of Zhuxianzhuang coal mine in Huaibei coalfield (Anhui, China). Issue 3 (16th March 2021) - Fang, Hongxia; Gui, Herong; Yu, Hao; Li, Jun; Wang, Meichen; Jiang, Yaqi; Wang, Chunlei; Chen, Chen
Abstract: In this study, profile Soil (0–10, 10–30, 30–60 cm) samples were collected and the content, horizontal and vertical distributions of Cr, Mn, Co, Ni, Cu, Zn, As, Cd, and Pb were analyzed. The results indicated that high concentrations of Cu-Zn appeared in wasteland B, while Co-Mn appeared in farmland. As the depth increased, Cr, Zn, and Cd contents in wasteland increased, Cu, As, Cr, and Pb contents in farmland also increased. The average concentrations of Cu, As, Zn, and Cd in wasteland and Cu, As, Mn, and Ni in farmland both exceeded their corresponding background values. Besides, the average concentrations of Cr, Mn, Co, Ni, Cu, and As of wasteland and farmland were much higher than the world soil background values except for Cd-Pb. The results of the assessment indicated that the contents of heavy metals in three lands have reached a slight pollution level. The results of Pearson correlation analysis and positive matrix factorization (PMF) showed that Cd was closely related to agricultural activities, As-Cr were mainly from mining activities, followed by domestic pollution. At the same time, Ni primarily came from domestic pollution, Cu, Zn, and Pb were related to transportation, Mn-Co were associated with nature factor.